Avoid and Rule: Selective Sociality Scale for Understanding Introverted Personality in a Digitally Socialized World - Waqar Husain; Achraf Ammar; Khaled Trabelsi; Aseel AlSaleh; Haitham Jahrami (European Journal of Investigation in Health, Psychology and Education, 2025)
(1) Background: The rapid expansion of information technology and globalization has significantly transformed psychosocial health, with excessive internet use and the pursuit of social acceptance via social media amplifying the impact of social factors, leading to both positive and negative psychological outcomes. This paper introduces “selective sociality,” a new psychological construct focused on mindful social engagement and digital interaction to maintain psychosocial health in the digital era, supported by a valid psychometric instrument: the Selective Sociality Scale (SSS). (2) Methods: The current research was conducted in a series of eight consecutive phases involving 1737 participants (Mean age = 24 years, SD = 7.66; women = 53.3%). The validation of the SSS involved exploratory and confirmatory factor analyses along with convergent, divergent, and predictive validity. (3) Results: The SSS demonstrated excellent reliability (α = 0.838; ICC = 0.954). The model fit indices, such as CFI (0.962), TLI (0.952), RMSEA (0.059), and SRMR (0.043), showed strong validity. The scale exhibited strong convergent validity with the Efficient Social Intelligence Scale. Selective sociality predicted positive personality traits and mental health but inversely predicted depression, anxiety, and stress. (4) Conclusions: The SSS offers valuable insights for both clinical practice and research.